A review on the impact of the worldwide shortage of glucagon-like peptide-1 medications on control of diabetic patients - Saiyed, Abrar A.; Darr, Mohammed Q.; Ghulam, Sahdia S. (International Journal Of Community Medicine And Public Health, 2024)
Glucagon-like peptide 1 receptor agonists (GLP-1 RA) have shown promising benefits in improving outcomes for patients with type 2 diabetes, particularly those affected by obesity-related complications such as cardiovascular disease, cardiometabolic disorders, and heightened cancer risks, posing significant public health challenges. Notably, GLP-1 RA have been recognized for their potential to achieve up to a 15% weight reduction over a span of two years, making them a preferred choice in specific conditions for diabetic patients with a body mass index (BMI) above 27. However, widespread public interest, particularly amplified through social media, has intensified the demand for GLP-1 RA due to their weight loss properties, thereby straining global supplies and fostering a black market among non-diabetic individuals seeking these effects. This heightened attention has prompted various medical regulatory bodies worldwide to enact strategies and policies aimed at alleviating shortages. Measures include minimizing new prescriptions of GLP-1 RA, exploring alternative medications within the GLP-1 RA category, carefully transitioning patients to other anti-diabetic treatments and managing patient expectations. These efforts appear effective in managing overall outcomes amid ongoing supply challenges. This narrative review provides a focused evaluation of how these GLP-1 RA medication shortages have impacted type 2 diabetic patients around the world and their overall diabetic outcomes.